Carbon Capture Storage System on the Ship - Imawan Santosa, Pramudya; Erifive, Pranata; Suardi, Suardi; Zaed Yuliadi, Mochamad; Pradityana, Atria; Ayu Nastiti, Yulia (Naval Architecture Department, Kalimantan Institut of Technology, 2025)
Carbon Capture and Storage (CCS) is one of the global warming mitigation technology systems by reducing CO2 emissions into the atmosphere. This system is a series of implementations of processes that are related to each other, starting from the separation and capture of CO2 from the source of exhaust emissions (flue gas), transportation of captured CO2 to storage (transportation), and storage to a safe place (storage). If these emissions are released in large quantities, it will certainly cause various problems such as Global Warming. In the maritime transportation sector, one of the emissions that is widely produced by ships is exhaust gas from the ship's main engine when operating which is released into the atmosphere through the Funnel (chimney). One method that can be done is to separate carbon dioxide gas (CO2) contained in the exhaust gas with Membrane Technology placed on the Funnel. Technical analyzes is done by testing the vessel model then the results are developed with naval theories. This article will discuss how to filter carbon dioxide gas and membrane technology that can be used on ships.